2018
DOI: 10.2147/cia.s168146
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between selected hormone and protein levels in serum and prostate tissue homogenates in men with benign prostatic hyperplasia and metabolic disorders

Abstract: PurposeThe purpose of the study was to assess the relationship between changes in the levels of selected hormones in serum and prostate tissue homogenate in regard to metabolic disorders in patients with diagnosed, surgically treated benign prostatic hyperplasia (BPH).Patients and methodsThe study involved a group of 154 men with a diagnosis of BPH with metabolic syndrome (MetS) and without MetS. The serum levels of the hormones – total testosterone, free testosterone, insulin, dehydroepiandrosterone sulfate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…One prospective study by Yue et al revealed that MetS may accelerate the clinical progression of BPH in middle-aged and older men (13). The conclusions reached by some other studies were also in line with Yue's study (14)(15)(16)(17)(18). However, a study that examined Korean men aged 50 years old proposed a conflicting conclusion (19), and relevant studies performed in Chinese (20), Japanese (21), and American (22) populations echoed this finding.…”
Section: Introductionmentioning
confidence: 82%
“…One prospective study by Yue et al revealed that MetS may accelerate the clinical progression of BPH in middle-aged and older men (13). The conclusions reached by some other studies were also in line with Yue's study (14)(15)(16)(17)(18). However, a study that examined Korean men aged 50 years old proposed a conflicting conclusion (19), and relevant studies performed in Chinese (20), Japanese (21), and American (22) populations echoed this finding.…”
Section: Introductionmentioning
confidence: 82%
“…In the present study, CCDC25 expression in cancerous tissues, as determined by immunohistochemistry, was correlated with serum CCDC25 level, suggesting that CCA cells are the major source of CCDC25 in the sera. Certain studies have reported that protein levels in serum samples may differ from protein expression levels in tissue due to a modification process during protein translocation (28,29). Therefore, to further validate that serum CCDC25 is mainly derived from CCA tissue, the association of serum and tissue CCDC25 expression levels should be verified using a larger number of paired samples.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have examined the effects of testosterone (T), DHT, and estrogen (E) upon BPH and LUTS. Their results, however, are not consistent [ 44 46 ].…”
Section: Discussionmentioning
confidence: 98%